Assessment of the impact of pre-slaughter handling and transportation on animal welfare and beef quality in Dendi and Welmara districts, Ethiopia - Amanuel Bekuma; Tekalign Tadesse (Cogent Food & Agriculture, 2024)
During transport from farms to abattoirs, animals may be subjected to un-favorable conditions leading to a compromise of animal welfare and reduced meat quality. The impact of pre-slaughter handling and transportation on animal welfare and beef quality was investigated in relation to Dendi and Welmara districts markets and abattoirs. Semi-structured questionnaires were used to gather detailed information on the pre-, during-, and post-slaughter processes from 200 respondents. 70 meat swab samples were collected from desirable animal parts to determine the microbial load, and 100 beef samples were used to evaluate the pH value. The majority of animals (55.9%) were transported via trekking, with 70% not receiving feed or water during transportation. Approximately 47% of beef was classified as Dark, Firm, and Dry (DFD) and was spoiled with microbial growth. The pH value of the meat was significantly affected by the distance traveled during transportation and the mode of transportation (P = 0.001). The mean log of the bacterial count of the sampled meat was 5.84-CFU log/100cm2, with the mean microbial load being statistically different (P < 0.05). Our findings suggest that animal welfare and beef quality were compromised due to stressful transportation, pre- and post-slaughter procedures, lack of facilities in marketing areas, and a poor abattoir system. Therefore, it is vitally necessary to issue relevant declarations, and legislation, and provide training on animal welfare awareness to various stakeholders.